Clinical characteristics and viral analysis of severe influenza A [H1N1]pdm09 in Guangzhou, 2019. Issue 6 (21st February 2022) - Dou, Min; Song, Wenjun; Lin, Yongping; Chen, Qigao; Lu, Chang; Liu, Zhongmin
Abstract: To understand the clinical characteristics of and analyze viral genes in patients with severe pneumonia due to [H1N1]pdm09 influenza virus in Guangzhou, 2019. The clinical data of 120 inpatients with laboratory‐confirmed influenza A [H1N1]pdm09 virus from January to March 2019 were collected and analyzed. The subjects were diagnosed according to the criteria of the "Diagnosis and Treatment Program of Influenza A H1N1 (third Edition 2009)" issued by the Ministry of Health and were divided into severe and nonsevere groups. Serum samples during fever were collected for cytokine analysis, and the viral genes were analyzed after the virus cultured in MDCK cells. The data were analyzed by SPSS 16 software, and the results of gene sequencing were analyzed by MEGA 6 software. Among the 120 inpatients, 36 (30%) were severe and 84 (70%) were nonsevere patients. The average age of severe patients was 53.11 ± 19.94 years, the average age of nonsevere patients, at 44.03 ± 24.47 years. There was no significant difference between the two groups ( p < 0.05). There were significant differences in the rates of moist rales and dyspnea in critically ill patients (p < 0.05). There were significant differences in the white blood cell count (WBC), lactate dehydrogenase (LDH), creatine kinase (CK), serum creatinine (sCr), procalcitonin (PCT) and C‐reactive protein (CRP) in severe patients with type A H1N1. Chest radiologic findings in severe patients showed ground glass shadows or pulmonary solid changes, and the difference was statistically significant for pulmonary fibrosis. Chronic lung disease (52.8%) and cardiovascular disease (27.8%) were independent risk factors for severe disease (p < 0.05). There were significant differences in secondary infections by Staphylococcus aureus (11.1%), pulmonary Aspergillus (22%) and Acinetobacter baumannii (16.7%) in critically ill patients ( p < 0.05). Serum IL‐8 in critically ill patients was significantly higher than those in nonsevere patients and healthy controls. The origin of virus strains in severe and nonsevere patients was the same, and there was no obvious mutation in the amino acid region of the antigenic site of the HA protein, but compared with the results of gene sequencing in previous years, the mutation sites showed a trend of annual accumulation. In conclusion, there was a high risk of severe pneumonia caused by H1N1 influenza A virus in Guangzhou in spring 2019. Long‐term continuous surveillance, prevention and control of the virus should be carried out to predict its epidemiology and distribution. Highlights: Patients infected with basic diseases, specially cardiovascular disease, tend to develop into severe diseases. Secondary infection makes the disease more complex and severe, the prevention of secondary infection should be considered, and active treatment with combined antibiotics should be taken. Changes in amino acid may alter the viral infectivity. To get more virus prevalence, whole‐genome sequencing can improve this. Cytokines IL‐8 and MIP‐1β can reflect the severity of severe patients. This study also accumulated data for the individualized treatment of severe patient.